Handling Fish at Fish Landing Places During Transportation To Several Fish Markets In Tobelo - Pattiasina, John Raimond; Kour, Femsy (Fakultas Pertanian, Universitas Muhammadiyah Maluku Utara, 2021)
This study aims to identify the handling of fish carried out by fishermen at the Tobelo fish landing site and during transportation to several markets in Tobelo. This study begins with direct observation of the auction and handling of fish at the fish landing site, then interviews with fishermen, fish traders and the Fisheries Service regarding the handling of fish after landing at the fish landing site, and observations made on the transportation facilities used by fish traders. The results of the research show that fishermen and fish traders have not done good handling of the catch, seen from the ice used is still lacking, namely a ratio of 1 3. The means of transportation used by fish traders are pick up cars, motorbikes and motorized tricycles. The means of transportation for pick up cars are equipped with ice, while motorbikes and motorized tricycles do not use ice in the coolbox because according to traders, the close distance to the market does not require ice and fish traders will add ice after arriving at the destination market.